IMPLEMENTASI PENGELOLAAN ADMINISTRASI PERSONALIA PADA PT. GANDA PRABU NUSANTARA PEKANBARU - Susiyanti Meilina (Ensiklopedia Social Review, 2020)
Implementation of personnel administration at PT. Ganda Prabu Nusantara begins with the process of human resource planning, the activities carried out to determine the human resource needs of a company. The purpose of this research is to: 1) find out how the implementation of personnel administration management at PT.Ganda Prabu Nusantara; 2) find out what are the obstacles encountered in the implementation of personnel administration management at PT. Ganda Prabu Nusantara; 3) find out what are the efforts made to overcome obstacles in the implementation of personnel administration management at PT. Ganda Prabu Nusantara Pekanbaru. This type of research is a qualitative study using descriptive methods, namely research that tries to describe, tell, and interpret a phenomenon that occurs at the present time. . The selection of informants in this study was chosen by incidental sampling, namely sampling by taking individuals who can be reached or met .. The type of data is primary data and secondary data collected through interviews, observation, and library research. The analysis technique used is qualitative analysis. The results of this study indicate that: the implementation of personnel administration management at PT. Ganda Prabu Nusantara Pekanbaru that the planning was carried out by the chief director and his senior staff in order to obtain a mature plan regarding the programs of PT. Ganda Prabu Nusantara going forward. The conclusion is the implementation of personnel administration management at PT. Ganda Prabu Nusantara is that in recruiting employees requires a workforce planning process, because there are no mistakes in recruiting employees in recruitment. The method used by PT. Ganda Prabu Nusantara is the open and closed method. In recruiting PT. Ganda Prabu Nusantara employees have certain criteria that must be possessed by prospective employees, although there are obstacles but there are efforts to overcome them. Suggestions: expected by the leadership of PT. Ganda Prabu Nusantara in carrying out personnel administration must be increased again in order to experience maximum performance improvement; there are trainings and there are adequate incentives for employees based on policies from the leadership.